Modification of transsternal occlusion of the main bronchus by plastic surgery of the anterior mediastinum with a mesh implant in the surgical treatment of widespread destructive pulmonary tuberculosis - R. V. Tarasov; S. S. Sadovnikova; E. V. Krasnikova; M. A. Bagirov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2023)
An observation from practice is given – surgical treatment of a patient with widespread destructive pulmonary tuberculosis due to a modified technique of transsternal occlusion of the main bronchus by plastic surgery of the anterior mediastinum with a mesh implant. Patient A., 37 years old, has been suffering from pulmonary tuberculosis for 2 years. She was admitted to the clinic with complaints of shortness of breath during exercise (mrc 3), cough, back pain. On computed tomography of the chest organs: a picture of fibrous-cavernous tuberculosis of the left lung with extensive mediastinal pulmonary hernia. The patient underwent transsternal occlusion of the left main bronchus with plastic surgery of the anterior mediastinum with a polymer mesh implant. The result of the treatment was the stabilization of the process and the clinical cure of the patient.